The role of hope in bullying and cyberbullying prevention - Hinduja, Sameer; Patchin, Justin W. (Frontiers in Sociology, 2025)
IntroductionResearch is clear that the cognitive-motivational internal asset of hope is significantly related to enhanced life satisfaction and psychological wellbeing. It has also shown promise in preventing participation in a variety of negative externalizing behaviors, especially antisociality, maladaptive coping, and various forms of aggression among young people. The current exploration evaluates the relationship between hope and youth participation in bullying and cyberbullying.Materials and methodsA nationally representative survey was conducted in spring 2019 among 5,569 U.S. students aged 12–17 (mean age 14.4) to examine bullying and cyberbullying offending, with 2,472 respondents completing Snyder's six-item Children's Hope Scale. The study measured participation in eight forms of school-based bullying and twelve forms of cyberbullying in the previous 30 days, and controlled for demographic variables including age, gender, race, and sexual orientation.ResultsThe study found that 16.5% of students participated in school bullying behaviors and 10.7% in cyberbullying behaviors in the previous 30 days. Name-calling was the most common form of school bullying (16%), while making others feel left out was the most frequent form of cyberbullying (10.1%). Statistical analyses revealed that male students were more likely to engage in both forms of bullying. Importantly, higher levels of hope were associated with significantly lower participation in both school bullying and cyberbullying behaviors.DiscussionFindings indicate that hope has an inverse relationship with school bullying and cyberbullying behaviors among US youth, suggesting that fostering hope could help reduce these forms of interpersonal aggression. Specifically, schools should prioritize hope-building through the cultivation of one-on-one relationships, the use of scenario-based learning, and the implementation of supportive-cooperative interventions.